1995
DOI: 10.1002/pola.1995.080330509
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of maleic anhydride‐functionalized polypropylene

Abstract: S.A. Direction Centrale des Recherches, Laboratoire Central, 31 0 rue de Ransbeek, B-1 120 Bruxelles, Belgium SYNOPSIS This work deals with the molecular characterization of maleic anhydride melt-functionalized polypropylene ( PP-g-MA). The functionalization mechanism, the nature, the concentration, and the location of grafted anhydride species onto the polypropylene chain are discussed. The polypropylene functionalization was performed using a pre-heated Brabender Plastograph ( 190°C, 4 min of mixing time). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
261
1
9

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(280 citation statements)
references
References 44 publications
7
261
1
9
Order By: Relevance
“…Em geral, as reações são feitas utilizando-se peróxidos, que geram radicais livres na cadeia polimérica, aos quais se adicionam moléculas polares [14] , tais como: fumarato de dietila [5] , anidrido maleico [9,15] , acetato de vinila [16] , ácido acrílico [17,18] , maleato de dietila [19,20] , anidrido itacônico [21] e isocianatos [22] . As primeiras etapas do mecanismo de incorporação de monômeros vinílicos ao PP são normalmente descritas na literatura como segue [23] : A quebra homolítica de cada molécula de peróxido orgânico produz dois radicais (Esquema 1), sendo que a velocidade de decomposição do peróxido depende somente da temperatura. Os radicais formados abstraem um átomo de hidrogênio da cadeia polimérica, produzindo macro-radicais.…”
Section: Palavras-chave: Funcionalização De Polipropileno Vinilsilanunclassified
“…Em geral, as reações são feitas utilizando-se peróxidos, que geram radicais livres na cadeia polimérica, aos quais se adicionam moléculas polares [14] , tais como: fumarato de dietila [5] , anidrido maleico [9,15] , acetato de vinila [16] , ácido acrílico [17,18] , maleato de dietila [19,20] , anidrido itacônico [21] e isocianatos [22] . As primeiras etapas do mecanismo de incorporação de monômeros vinílicos ao PP são normalmente descritas na literatura como segue [23] : A quebra homolítica de cada molécula de peróxido orgânico produz dois radicais (Esquema 1), sendo que a velocidade de decomposição do peróxido depende somente da temperatura. Os radicais formados abstraem um átomo de hidrogênio da cadeia polimérica, produzindo macro-radicais.…”
Section: Palavras-chave: Funcionalização De Polipropileno Vinilsilanunclassified
“…As seen in this figure the FT-IR spectrum of PP-g-MA shows the absorption band at (1700-1740cm -1 ) that is due to the presence of DCP and absorption bands at (1760-1800cm -1 ) and around 1850cm -1 can be assigned to grafted anhydride because an intense absorption band near 1785cm -1 and a weak absorption band near 1850cm -1 is due to symmetric and asymmetric C=O stretching respectively. [8], [14], [15]. It has been shown that the intensity of peaks increased by increasing the DCP content from 1 to 4 phr that lead to increase the graft percentage but it decreased by more adding of DCP (6phr) that may be due to decomposition effect of initiator.…”
Section: Ft-ir Spectroscopymentioning
confidence: 99%
“…In fact, these kinds of grafted polymers have been widely used to improve interfacial adhesion between the components in polymer blends [2]- [7]. Maleic anhydride has been used recently for the functionalization of polyolefins due to the higher reactivity of the anhydride group toward successive reactions [8]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Free radical grafting of maleic anhydride (MA) onto polyolefins has gained wide industrial application. [15][16][17] MA modified polyolefins are an essential part of many plastics formulations. They are used as chemical coupling agents, impact modifiers, and compatibilisers for blends and filler reinforced systems.…”
Section: Introductionmentioning
confidence: 99%